PENGARUH EDUKASI KESEHATAN REPRODUKSI TERHADAP PENGETAHUAN DAN SIKAP REMAJA TERHADAP PERILAKU SEKSUAL PRANIKAH DI SMKN 11 KABUPATEN TANGERANG - ZAYANI, NOFRI; SUSANTO, BELA NOVITA AMARIS (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2024)
Actions that can be risky for adolescent reproductive health are engaging in premarital sexual behavior, drug abuse, violence, dating, smoking, drinking alcohol, and others. Premarital sexual behavior often results in unwanted pregnancies, contracting sexually transmitted diseases (STDs), abortion, and maternal death. One form of preventive action to maintain adolescent reproductive health today is to provide education or counseling with media that is interesting and liked by students such as animated videos. The purpose of the study was to determine the effect of providing reproductive health education with animated video media on adolescent knowledge and attitudes related to premarital sexual behavior at SMKN 11 Tangerang Regency. This research method used a quasi-experimental design with a one group pretest-posttest design. The population of this study was 125 class X students of SMKN 11 Tangerang Regency. Sampling used a random sampling technique so that the number of samples was 25 people who were adjusted to the research inclusion criteria. The research instrument used a questionnaire. Data processing was carried out using paired ¬t-tests at α = 5%. The results of the study showed an increase in knowledge from good as many as 5 people (20%) to 24 people (96%), sufficient as many as 15 people (60%) to 1 person (4%), lacking as many as 5 people (20%) to 0% after providing reproductive health education. The results of the T-test showed that there was an effect of providing health education on the knowledge and attitudes of adolescents regarding premarital sexual behavior at SMKN 11 Tangerang Regency (p-value = 0.0001 ≤ α = 0.05). In conclusion, providing reproductive health education has an effect on the knowledge and attitudes of adolescents towards premarital sexual behavior at SMKN 11 Tangerang Regency.